‘Tails’ – A fairy tale on furry tails: A 15-year theatre experience for hospitalized children created by health professionals - Rokach, Ami (Pulsus Group Inc, 2007)
OVERVIEW: The present article describes an innovative theatre production that has been running in The Hospital for Sick Children in Toronto, Ontario, for the past 15 years. It is directed at, and created for, hospitalized children and their families. The effects of hospitalization on children and their families are reviewed, and the benefits of humour and support during the stressful time the children have to spend in the hospital is highlighted. The play and its message, as well as possible health benefits, are also described. PRACTICAL IMPLICATIONS: Theatre productions may help ease the anxiety felt by children and their families concerning illness, hospitalization and the associated medical procedures. Theatre may also assist in increasing patients’ compliance with medical procedures and follow-up. ORIGINALITY: The play described is the first regular children’s theatre created by medical staff for hospitalized children. It is valuable because it may result in other hospitals following this example, and because it may generate research on the effects of theatre on patients and their families.